Preventative Effect of Traditional Medicine Anar-5 on the Development of Chronic Gastritis in a Rat Model - Dashzeveg, Uranzaya; Buyantogtokh, Dejidmaa; Adilbish, Altanchimeg; Chimedtseren, Chimedragchaa; Purevjav, Batkhuyag (Central Asian Journal of Medical Sciences, 2018)
Objective: To study the effect of traditional medicine Anar-5 on the development of chronic gastritis in rat gastric mucosa. Methods: Rats were orally administered deoxycholate sodium 1ml/100 gm or a combination of deoxycholate 1 ml/100 gm and Anar-5 at Anar-5 100 mg/kg or 200 mg/kg for 4, 8, and 12 weeks to determine the protective effect of Anar-5. Serum gastrin levels were measured to determine the impact of Anar-5. Gastric specimens were prepared for light microscopy with hematoxylin and eosin and PAS stains. The damage of barrier in mucosa with erosion or ulceration, and the thickness of mucin were examined using light microscopy. The serum levels of gastrin were measured with ELISA method. Results: Under light microscopy, the gastric mucosa was diffusely eroded or ulcerated and the thickness of mucin was decreased in rats not treated with Anar-5. The levels of gastrin in serum were significantly lower in chronic atrophic gastritis rats than that in normal rats (p<0.05). Doubling the dose of Anar-5 from 100 mg/kg to 200 mg/kg made no difference. Conclusion: Treatment with Anar-5 prevented chronic gastritis and gastric atrophy.